Health Promoting Behaviors among Adolescents at Selected Schools of Chitwan - Pokharel, Silaja; Bajracharya , Subina (Journal of Nepal Health Research Council, 2024)
Background: Health Promotion and maintenance are fundamental prerequisites to achieve optimum health in an individual and limit the illness. The objective of the study was to assess the health promoting behaviors among adolescents at selected schools. Methods: A descriptive cross-sectional study was conducted among 238 adolescents age 14-18 years of age studying in three different government schools of Bharatpur-10 Chitwan. Probability simple random method was used for selecting the required respondent. Data were collected using Adolescents Health Promoting Scale questionnaire through self-administered technique. Obtained data were analyzed using descriptive and inferential statistics. Results: The study revealed that 47.5% had high level of health promoting behaviors whereas 52.5% had low level of health promoting behavior. Regarding, the subscale, the highest score was obtained in the area of exercise (median percentage=72.5%) and lowest score was obtained in the area of stress management (median percentage=48%). Moreover, statistically significant variables for health promoting behavior were respondents age, availability of school health nurse, educational status of both the parents and and occupation of father (p<0.05). Conclusions: More than half of the adolescents in schools have low health promoting behavior, particularly in the area of stress management and nutrition. Adolescence is the period when most of the healthy and unhealthy habits are developed. Hence, it is necessary to focus on developing efficient health promotion and disease prevention strategies in collaboration with school teachers and school health nurse. Keywords: Adolescent; adolescent health; health promotion; health promoting behavior; school health.